2018
DOI: 10.1101/294751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of the Resuscitation-Availability of Viable-But-Nonculturable Cells ofVibrio parahaemolyticusupon Exposure to the Refrigerator Temperature

Abstract: 27Major pathogenic strains of Vibrio parahaemolyticus can enter into the viable-but-28 nonculturable (VBNC) state when subjected to environmental conditions commonly 29 encountered during food processing. Especially, VBNC cells can be recovered to the 30 culturable state reversibly by removing the causative stress, expressing higher levels of 31 virulence factors. Therefore, the aim of this study was to determine if VBNC V. 32 parahaemolyticus strains retain the resuscitation-availability upon eliminating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Several methods and processes have been reported for the resuscitation of viable, but no culturable bacteria, such as the use of diluted or semi-solid media (Wai et al, 2000;Whitesides & Oliver, 1997), the addition of some components such as catalase, sodium pyruvate, or α-ketoglutarate or by adding fertilizers, such as decaying phytoplankton (Collin & Hernroth, 2020;Morishige et al, 2013;Yoon et al, 2018). However, the resuscitation results are not always successful and depend on the species, the cells physiological state, and the duration of time for which the cells remained into the VBNC state (Oliver, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several methods and processes have been reported for the resuscitation of viable, but no culturable bacteria, such as the use of diluted or semi-solid media (Wai et al, 2000;Whitesides & Oliver, 1997), the addition of some components such as catalase, sodium pyruvate, or α-ketoglutarate or by adding fertilizers, such as decaying phytoplankton (Collin & Hernroth, 2020;Morishige et al, 2013;Yoon et al, 2018). However, the resuscitation results are not always successful and depend on the species, the cells physiological state, and the duration of time for which the cells remained into the VBNC state (Oliver, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Many authors claim that the recovery of cells observed in most cases is due to the regrowth of some remaining culturable cells [ 17 , 18 ]. Other studies showed that cells in a dormancy state can also resuscitate [ 19 , 20 , 21 , 22 ] when conditions are favourable. Most probably, regrowth and resuscitation co-exist.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, cells that enter the VBNC state retain their metabolic activity and membrane integrity [3][4][5] , however they lost their ability to regrow immediately on a medium that typically supports proliferation [6][7][8][9][10] . Several studies demonstrated that VBNC cells can be resuscitated with appropriate environmental stimuli or permissive growth conditions [10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%